Preparation and characterization of calcium alginate-chitosan complexes loaded with lysozyme. (September 2018) - Wu, Tiantian; Li, Yuan; Shen, Ni; Yuan, Chunhong; Hu, Yaqin
Abstract: The objective of this study was to study the effect of calcium ions on the binding of lysozyme to chitosan (CS)/sodium alginate (SA) complexes (CS-SA-Ps), in order to develop a complex system for lysozyme delivery which might be of practical interest in the field of food preservatives. Result showed that with the increase of calcium ions (Ca 2+ ) concentration, the value of Z-Ave decreased while the value of ζ-potential and LE increased, where the addition of 5.0 mM Ca 2+ contributed to uniform distribution of the complexes. Sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) revealed that there was no significant difference of molecular integrity when lysozyme was released from CS-SA-Ps. The exothermic interaction between lysozyme and SA were proved by thermodynamic measurements, in which the binding stoichiometry showed a slight decrease in the presence of calcium chloride. Moreover, the release rate of lysozyme from CS-SA-Ps could be slowed by the increase of Ca 2+ addition concentration. Highlights: Effects of calcium ions on the properties of particles were discussed. The binding of lysozyme to SA was self-assembled via exothermic interactions. Lysozyme released from CS-SA-Ps showed a slow and sustained release and followed non-Fickian mechanism.